2010
DOI: 10.1097/aog.0b013e3181e238f0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Menstrual Cycle and Hormonal Contraceptives on Human Papillomavirus Detection in Young, Unscreened Women

Abstract: OBJECTIVE:To estimate the effect of the menstrual cycle and oral contraceptive pill (OCP) use on the prevalence, incidence, and persistence of human papillomavirus (HPV). METHODS:A longitudinal study was conducted among 2,065 women aged 18 -29 years. The women returned a self-collected cervicovaginal sample and filled out a questionnaire. A total of 1,812 women participated at all three time points, month 0, month 6, and month 12. RESULTS:Low-and high-risk HPV prevalence at study entry was 8.9% and 11.8%, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
1
17
1
Order By: Relevance
“…After controlling for plausible confounding factors, prolonged oral contraceptive consumption was found to be inversely associated with the risk of CIN in Australian women, consistent with a previous report of a decreased risk of CIN with use over 5 years [17]. The potentially protective mechanism may be attributable to the hormonal effect of oral contraceptive on HPV DNA expression and the viscosity of the cervical mucus [18,19]. Estrogen can protect the mucosal immune system against early HPV infection [17], while the viscosity of the mucus affects the penetration of foreign bodies including HPV [19].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…After controlling for plausible confounding factors, prolonged oral contraceptive consumption was found to be inversely associated with the risk of CIN in Australian women, consistent with a previous report of a decreased risk of CIN with use over 5 years [17]. The potentially protective mechanism may be attributable to the hormonal effect of oral contraceptive on HPV DNA expression and the viscosity of the cervical mucus [18,19]. Estrogen can protect the mucosal immune system against early HPV infection [17], while the viscosity of the mucus affects the penetration of foreign bodies including HPV [19].…”
Section: Discussionsupporting
confidence: 83%
“…The potentially protective mechanism may be attributable to the hormonal effect of oral contraceptive on HPV DNA expression and the viscosity of the cervical mucus [18,19]. Estrogen can protect the mucosal immune system against early HPV infection [17], while the viscosity of the mucus affects the penetration of foreign bodies including HPV [19]. The inverse association of the risk of CIN with long term oral contraceptive consumption could also be due to the relatively stable sexual relationships among middle-aged women, who tended to prefer oral contraception to the use of condoms [20].…”
Section: Discussionmentioning
confidence: 99%
“…28,29 HPV detection with self-sampling showed a good concordance with physician-sampling, and is highly accepted by women. Self-sampling is therefore a suitable method to study HPV incidence and clearance among a large group of young women.…”
Section: Methodsmentioning
confidence: 99%
“…Due to small numbers of re-infection/reactivation, potential factors of influence could not be analyzed. The mean age of the women was 23.5 years [18][19][20][21][22][23][24][25][26][27][28][29]. At baseline almost all women (94.3%) were sexually active and the mean sexual age (i.e., years of being sexually active) was 6.8 years .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] A recent study exploring the effect of oral contraceptive (OC) use on HPV detection revealed a higher detection rate during the follicular phase among non-users, whereas OC users experienced a higher detection rate during the luteal phase. 7 Using data collected in the Ludwig-McGill cohort study conducted in Brazil, we evaluated the effect of menstrual phase on HPV detection, and attempted to validate previous findings concerning OC use.…”
Section: Introductionmentioning
confidence: 99%